Development and validation of an Organizational Citizenship Behaviour measurement scale for Indonesian employees: Exploratory and Confirmatory Factor Analysis - Hardiansyah Hardiansyah; Rabiatul Adhawiyah; Lisbet Sitomorang (Psikostudia : Jurnal Psikologi, 2025)
This study aims to develop a measurement tool for organizational citizenship behaviour (OCB) that is grounded in the cultural values of Indonesian workers. Utilising a quantitative research design focused on instrument construction, the study involved 381 participants selected through accidental sampling. Data analysis employed content validity indices (I-CVI and S-CVI), as well as exploratory and confirmatory factor analyses. The results of content validity indicated that the statement items were appropriate for use, and the developed instrument demonstrated good validity and reliability. The instrument's structure consists of four dimensions: willingness to help coworkers, adherence to social norms, tolerance, and maintaining social harmony. The organizational citizenship behavior measuring tool consists of 12 items, with a reliability value of 0.782. The findings enrich the concept of OCB, particularly with the emergence of new dimensions, such as maintaining social harmony and tolerance, which reflect the collectivist values and workplace harmony inherent in Indonesian work culture. This instrument can be utilised by organizations in Indonesia to measure employee OCB more accurately, which can assist in human resource development planning.Penelitian ini bertujuan mengembangan alat ukur organizational citizenship behavior yang berbasis pada nilai-nilai budaya pekerja Indonesia. Penelitian ini menggunakan desain kuantitatif dengan fokus pada konstruksi alat ukur, dengan jumlah partisipan sebanyak 381 dipilih dengan teknik accidental sampling. Analisis data menggunakan indeks validitas isi (I-CVI dan S-CVI), eksploratory factor analysis dan confirmatory factor analysis. Hasil validitas isi menunjukkan bahwa item pernyataan layak untuk digunakan, dan instrumen yang dikembangkan memiliki validitas dan reliabilitas yang baik, dengan struktur empat dimensi yaitu kesediaan membantu rekan kerja, kepatuhan terhadap norma sosial, toleransi dan menjaga harmoni sosial. Alat ukur organizatioonal citizenship behavior memiliki 12 item dengan nilai reliabilitas 0,782. Temuan penelitian memperkaya konsep OCB khususnya dengan munculnya dimensi baru seperi menjaga harmoni sosial dan toleransi yang mencerminkan nilai-nilai kolektivisme dan kerukunan dalam budaya kerja Indonesia.  Instrumen yang dikembangkan dapat digunakan oleh organisasi di Indonesia untuk mengukur OCB pegawai secara lebih akurat, yang nantinya dapat membantu dalam perencanaan program pengembangan SDM.